Positive electrode material and preparation method thereof, positive electrode plate and secondary battery
By controlling the proportion of cracks and the particle length-to-size ratio in the positive electrode material, the problem of poor gas production effect and stability of the positive electrode material during the circulation process is solved, and higher circulation stability and capacity are achieved.
Patent Information
- Application Number
- CN202411940209.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing positive electrode materials have obvious gas production effects during the charge and discharge cycle, and the circulation stability is poor.
The structure and performance of the material are optimized by controlling the proportion of cracks in the positive electrode material between 1.5% and 11%, and the average aspect ratio M/N of a single particle is within the range of 1≤M/N≤1.6.
It effectively reduces the gas production of the cathode material during the battery circulation process, improves the circulation stability and long-term circulation performance of the material, and maintains good capacity.
Smart Images

Figure CN119481036A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] At present, among many positive electrode materials, ternary positive electrode materials have become the most widely used positive electrode materials in the field of lithium-ion batteries due to their advantages of high specific capacity and high voltage platform. However, the current positive electrode materials have the disadvantages of obvious gas generation effect and poor cycle stability during the charge and discharge cycle. Summary of the invention
[0003] In view of this, in order to solve at least one of the above defects, it is necessary to provide a positive electrode material.
[0004] In addition, it is also necessary to provide a method for preparing the aforementioned positive electrode material, and a positive electrode sheet and a secondary battery using the aforementioned positive electrode material.
[0005] In a first aspect, an embodiment of the present application provides a positive electrode material, in which the ratio of the number of particles with cracks in the positive electrode material to the total number of particles is 1.5%~11%, and the average aspect ratio M / N of the particles of the positive electrode material satisfies: 1≤M / N≤1.6, wherein M is the length of the longest straight side of a single particle, and N is the length of the straight side perpendicular to the midpoint of the longest straight side.
[0006] In some possible embodiments, the positive electrode material has an XRD diffraction peak in the range of 44° to 45°, and the half-peak width of the XRD diffraction peak is 0.150° to 0.200°.
[0007] In some possible embodiments, the number of particles satisfying 1≤M / N≤1.6 in the positive electrode material accounts for no less than 90%.
[0008] In some possible embodiments, the general formula of the positive electrode material is as follows: Li a Ni x Co y N 1-x-y-b Y b O2, wherein 0.95≤a≤1.05, 0.5≤x<1, 0≤y≤0.30, 0.001≤b≤0.01, the N element includes at least one of Mn and Al, and the Y element includes at least one of Al, Ti, Zr, Sr, Mg, Y, Ba, Cu, W, Nb, La, Ce, Mo, Sn, Ta and Ca.
[0009] In some possible embodiments, the Y element includes at least a Y1 element and a Y2 element, the Y1 element includes at least one element of Zr, Sr, Ba and Ca, and the Y2 element includes at least one element of Al, Ti, Mg, Y, Cu, W, Nb, La, Ce, Mo, Sn and Ta.
[0010] In some possible embodiments, the mass percentage of the Y element in the positive electrode material is 0.01 wt % to 0.5 wt %.
[0011] In some possible embodiments, the positive electrode material includes a plurality of primary particles, and the average particle size of the primary particles is 1 μm to 6 μm.
[0012] In some possible embodiments, the positive electrode material is a single crystal material, the positive electrode material contains single grains with the same orientation, and the average grain size of the single grains is 1 μm to 6 μm.
[0013] In some possible embodiments, the particle size of the positive electrode material satisfies: min <1μm,2.0μm<D V,50 <4.5μm, D max <15μm,0.8<(D V,90 -D V,10 ) / D V,50 <1.6.
[0014] In some possible embodiments, the specific surface area of the positive electrode material is 0.1 m 2 / g ~1.6 m 2 / g.
[0015] In some possible embodiments, the oil absorption value of the positive electrode material per 100 grams is 10 mL to 40 mL.
[0016] In some possible embodiments, the residual alkali on the surface of the positive electrode material satisfies: LiOH≤0.5wt%, Li2CO3≤0.5wt%.
[0017] In some possible embodiments, the compaction density of the positive electrode material is 2.5 g / cm 3 ~3.6g / cm 3 .
[0018] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps: mixing a precursor, a lithium salt and an additive to form a mixture, and sintering the mixture once to obtain a primary sintered product; crushing the primary sintered product, and performing a secondary sintering on the crushed primary sintered product, wherein the secondary sintering is a multi-stage gradient temperature sintering process to obtain a secondary sintered product; crushing the secondary sintered product to obtain a crushed secondary sintered product; and mixing the crushed secondary sintered product with a coating agent and sintering to obtain the positive electrode material, wherein the ratio of the number of particles with cracks in the positive electrode material to the total number of particles is 1.5%~11%, and the average aspect ratio M / N of the particles of the positive electrode material satisfies: 1≤M / N≤1.6, wherein M is the length of the longest straight side of a single particle, and N is the length of the straight side perpendicular to the midpoint of the longest straight side.
[0019] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material as described above or a positive electrode material prepared by the positive electrode material preparation method as described above.
[0020] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material as described above or the positive electrode material prepared by the method for preparing the positive electrode material as described above.
[0021] The positive electrode material provided in the embodiment of the present application can effectively reduce the gas production of the positive electrode material during the battery cycle by controlling the proportion of the number of cracks in the positive electrode material to 1.5%~11%. In addition, by controlling the average aspect ratio M / N of a single crystal particle in the positive electrode material to satisfy 1≤M / N≤1.6, the aspect ratio of the crystal particles within this range is relatively low, and the crystal particles with a low aspect ratio have a high roundness. The improved roundness is conducive to reducing the specific surface area of the positive electrode material, and the smaller specific surface area is conducive to reducing the direct contact between the positive electrode material and the electrolyte, thereby reducing the generation of side reactions, and is conducive to improving the long-term cycle performance, high temperature storage performance and gas production performance of the positive electrode material. Therefore, the present application can effectively improve the cycle performance of the positive electrode material and improve the gas production performance by controlling the proportion of the number of cracks in the positive electrode material and the aspect ratio of a single crystal particle, while also ensuring that the positive electrode material has a good capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.
[0023] Figure 2It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.
[0024] Figure 3 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Example 1 of the present application at a magnification of 3000 times.
[0025] Figure 4 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Comparative Example 1 at a magnification of 3000 times.
[0026] Figure 5 This is a cross-sectional SEM photograph of the positive electrode material of Example 1 of the present application at a magnification of 5000 times.
[0027] Figure 6 This is a cross-sectional SEM photograph of the positive electrode material of Comparative Example 1 at a magnification of 5000.
[0028] Figure 7 50-cycle capacity retention curve of batteries prepared with the positive electrode materials of Example 1 and Comparative Example 1 of the present application.
[0029] Figure 8 This is a comparison chart of the gas production of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present application. DETAILED DESCRIPTION
[0030] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0031] Since the cycle life of existing positive electrode materials is not ideal and they are prone to gas generation, and the existing solutions have relatively simple means of controlling particles, it is difficult to fully utilize the advantages of the particles.
[0032] The inventors of this application studied the particle morphology of the positive electrode material and found that the performance of the positive electrode material is greatly affected by the number of cracks in the particles and the roundness of the particles. When there are too many cracks in the positive electrode material, the intercrystalline displacement during the cycle process will cause the particles to expose new surfaces. In addition, particles with a large aspect ratio have poor roundness and will break during the electrode rolling process, exposing more new surfaces. These newly exposed surfaces will react with the electrolyte, resulting in deterioration of the cycle performance and gas production performance.
[0033] To this end, an embodiment of the present application provides a positive electrode material, in which the ratio of the number of particles with cracks to the total number of particles is 1.5%~11%, and the average aspect ratio M / N of single crystal particles of the positive electrode material satisfies: 1≤M / N≤1.6, wherein M is the length of the longest straight side of a single particle, and N is the length of the straight side perpendicular to the midpoint position of the longest straight side.
[0034] First of all, the sources of cracks in the positive electrode material are mainly unit cell anisotropy, process control of material crushing, and intercrystalline displacement after cycling, while the cracks in the positive electrode material of the present application mainly come from unit cell anisotropy and cracks generated during the crushing process. It should be noted that the cracks in the present application refer to cracks with a size between 0.5nm and 30nm. The present application controls the proportion of the number of cracks in the positive electrode material within the range of 1.5% to 11%, which can effectively reduce the gas production of the positive electrode material during the battery cycle. When the proportion of cracks in the positive electrode material is ≤1.5%, the crystal is too round, resulting in a low compaction density of the powder of this type of positive electrode material, which in turn leads to a low compaction density of the pole piece; when the proportion of cracks in the positive electrode material is >11%, there are too many crystal cracks. After this type of positive electrode material is prepared into a battery, the gas production of the battery will be significantly deteriorated during the cycle. Illustratively, the proportion of cracks in the positive electrode material can be 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, or any value within the range formed by any two of the above values.
[0035] Although the present application controls the number of cracks in the positive electrode material, the positive electrode material may still break during the rolling process of the pole piece, produce fine powder, and cause gas production. To this end, under the premise of controlling the proportion of the number of cracks in the material, the present application further controls the average aspect ratio M / N of the individual particles in the positive electrode material to satisfy 1≤M / N≤1.6. The aspect ratio of the particles within this range is relatively low, and the particles with low aspect ratio have a higher roundness. The improved roundness is conducive to reducing the specific surface area of the positive electrode material, and the smaller specific surface area is conducive to reducing the direct contact between the positive electrode material and the electrolyte, thereby reducing the generation of side reactions, which is conducive to improving the cycle performance of the positive electrode material. In addition, the lower aspect ratio can also reduce the breakage of the positive electrode material during the rolling process of the pole piece and improve the gas production performance. Exemplarily, the aspect ratio of the particles can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 or any value within the range composed of any two of the above values.
[0036] Therefore, the present application can effectively improve the cycle stability of the positive electrode material, improve the cycle performance of the material, and increase the compaction density of the electrode sheet, so that the positive electrode material has a good capacity, and at the same time effectively reduce the gas production after the positive electrode material is prepared into a battery.
[0037] In some embodiments, in the XRD spectrum of the positive electrode material, the positive electrode material has a diffraction peak within 44°~45°, and the half-peak width of the diffraction peak is 0.150°~0.200°. Within the above half-peak width value range, the unit cell size of the positive electrode material is moderate, which is conducive to the capacity of the positive electrode material. The half-peak width of the XRD diffraction peak further ranges from 0.155° to 0.175°. Exemplarily, the half-peak width of the XRD diffraction peak can be 0.150°, 0.155°, 0.160°, 0.165°, 0.170°, 0.175°, 0.180°, 0.185°, 0.190°, 0.195°, 0.200° or any value within the range composed of any two of the above values.
[0038] In some embodiments, the positive electrode material is a single crystal material, and the positive electrode material contains single particles with the same orientation. Single particles with the same orientation are primary particles. The positive electrode material includes a plurality of primary particles, the primary particles have good dispersibility, and the average particle size of the primary particles is 1 μm to 6 μm. The primary particles within the above range have a moderate particle size, which is conducive to the full utilization of the capacity of the positive electrode material, and the primary particles have good dispersibility, grow more fully, and form fewer agglomerates, which is conducive to improving the cycle performance of the positive electrode material. The average particle size of the primary particles is further 1.5 μm to 3 μm. Exemplarily, the average particle size of the primary particles can be 1 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.1 μm, 2.4 μm, 2.7 μm, 3 μm, 3.1 μm, 3.4 μm, 3.5 μm, 3.7 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm or any value within the range composed of any two of the above values.
[0039] In some embodiments, the number of crystal particles satisfying 1≤X / Y≤1.6 in the positive electrode material accounts for more than 90%. By controlling the aspect ratio of more than 90% of the crystal particles in the material to be within the range of 1 to 1.6, it is beneficial to improve the roundness of the overall particles in the positive electrode material, so as to further reduce the specific surface area of the positive electrode material and reduce the generation of side reactions, thereby further improving the long-term cycle performance, high-temperature storage performance and gas production performance of the positive electrode material. Exemplarily, the number of crystal particles satisfying 1≤X / Y≤1.6 in the positive electrode material can account for 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, etc.
[0040] In some embodiments, the median particle size D of the positive electrode material V,50 2μm~4.5μm. Median particle size D V,50Indicates the particle size of the material particles corresponding to the cumulative particle size distribution percentage reaching 50% volume ratio. This application controls the median particle size of the positive electrode material within the above appropriate range, and the particle size is moderate, which is beneficial to reducing the specific surface area of the particles and reducing the side reactions between the particles and the electrolyte, thereby improving the safety and cycle life of the material; at the same time, the particles of the above size range are also beneficial to reducing the internal stress of the particles and reducing the risk of electrochemical polarization of lithium ions inside and outside the particles, thereby improving the capacity of the positive electrode material. The minimum particle size D of the positive electrode material min <1μm, maximum particle size D max <15μm, where the smallest particle size in the positive electrode material is below 1μm, and the largest particle size is less than 15μm. The presence of particles smaller than 1μm is beneficial to improving the compaction density and capacity of the positive electrode material. The maximum particle size is controlled below 15μm to reduce the number of large agglomerates and affect the cycle performance. For example, the median particle size D of the positive electrode material V,50 It is 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm or any value within the range formed by any two of the above values.
[0041] In some embodiments, the positive electrode material has a 0.8≤(D V,90 -D V,10 ) / D V,50 ≤1.6.D V,10 In the particle size distribution, it shows the particle size corresponding to the cumulative particle size distribution reaching 10%, that is, in the particle group, 10% of the particles are smaller than this particle size. Usually, D V,10 Used to describe the finer particles in a particle group. V,90 It indicates the particle size corresponding to 90% of the cumulative particle size distribution. That is to say, in the particle group, 90% of the particles are smaller than this particle size. V,90 Usually used to describe coarser particles in a particle group. (D V,90 -D V,10 ) / D V,50 Indicates the width of the particle size distribution in the positive electrode material. This application controls 0.8≤(D V,90 -D V,10 ) / D V,50 ≤1.6, the particle size distribution of the positive electrode material is moderate, which can reduce the specific surface area of the particles while maintaining the compaction density of the material, thereby ensuring that the positive electrode material has excellent cycle performance, storage performance and capacity. V,90 -D V,10 ) / D V,50 It can be 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 or any value within the range formed by any two of the above values.
[0042] This application satisfies the following requirements by controlling the particle size of the positive electrode material: min <1μm,2.0μm<D V,50 <4.5μm, D max <15μm,0.8<(D V,90 -D V,10 ) / D V,50 <1.6, the particle size of the positive electrode material can be moderate, so that the compaction density of the material can be maintained while reducing the specific surface area of the particles, which is beneficial to ensure that the positive electrode material has excellent cycle performance, storage performance and capacity.
[0043] In some embodiments, the specific surface area of the positive electrode material is 0.1 m 2 / g ~1.6 m 2 / g, the crystal particles in the positive electrode material have a smaller aspect ratio, the particles are more rounded, and the specific surface area is smaller. The small specific surface area is beneficial to reduce the direct contact between the positive electrode material and the electrolyte, thereby reducing the generation of side reactions, and is beneficial to improving the long-term cycle performance, high temperature storage performance and gas production performance of the positive electrode material. Exemplarily, the specific surface area of the positive electrode material can be 0.1 m2 / g, 0.2 m2 / g, 0.3 m2 / g, 0.4 m2 / g, 0.5 m2 / g, 0.6 m2 / g, 0.7 m2 / g, 0.8 m2 / g, 0.9 m2 / g, 1.0 m2 / g, 1.1 m2 / g, 1.2 m2 / g, 1.3 m2 / g, 1.4 m2 / g, 1.5 m2 / g, 1.6 m2 / g or any value within the range formed by any two of the above values. Furthermore, the specific surface area of the positive electrode material is further 0.6 m 2 / g ~1.2 m 2 / g.
[0044] In some embodiments, the oil absorption value per 100 grams of the positive electrode material is 10 mL to 40 mL. A lower oil absorption value is beneficial to improving the processing performance of the positive electrode material. Exemplarily, the oil absorption value per 100 grams of the positive electrode material can be 10 mL, 15 mL, 20 mL, 25 mL, 30 mL, 35 mL, 40 mL, or any value within the range formed by any two of the above values.
[0045] In some embodiments, the compaction density of the positive electrode material under 3t pressure is 2.5 g / cm 3 ~3.6g / cm 3 By controlling the number of cracks in the material and the aspect ratio of the crystal particles, the compaction density of the positive electrode material powder can be effectively increased, thereby ensuring that the positive electrode material has a higher compaction density after being made into a pole piece, thereby increasing the capacity of the positive electrode material. For example, the compaction density of the positive electrode material can be 2.5g / cm3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 、3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 , 3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 、3.6g / cm 3 Or any value within the range formed by any two of the above values.
[0046] In some embodiments, the residual alkali of the positive electrode material is LiOH < 0.5wt%, Li2CO3 < 0.5wt%. By controlling the number of cracks in the positive electrode material and the aspect ratio of the crystal particles, it is beneficial to reduce the specific surface area of the particles while increasing the compaction density of the material, so as to reduce the alkalinity of the material and improve the storage performance. At the same time, the residual alkali on the surface of the particles is reduced, which effectively improves the electrochemical activity of the positive electrode material and ensures the smooth diffusion of lithium ions in the material, thereby improving the battery performance. Exemplarily, the residual alkali amount can be 0.01wt%, 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.35wt%, 0.5wt% or any value within the range formed by any two of the above values.
[0047] In some embodiments, the general formula of the positive electrode material is as follows: Li a Ni x Co y N 1-x-y-b Y b O2, wherein 0.95≤a≤1.05, 0.5≤x<1, 0≤y≤0.30, 0.001≤b≤0.01, N element includes at least one of Mn and Al, and Y element includes at least one of Al, Ti, Zr, Sr, Mg, Y, Ba, Cu, W, Nb, La, Ce, Mo, Sn, Ta and Ca. By doping the positive electrode material with the above elements, the crystal structure of the positive electrode material can be optimized, the surface morphology of the single crystal particles can be further improved, cracks can be reduced, and the particles can be controlled to have a lower aspect ratio, making the particles more rounded, and the structural stability and conductivity of the positive electrode material can be further improved.
[0048] In some embodiments, the mass proportion of the Y element in the positive electrode material is 0.01wt%~0.5wt%. For example, the mass proportion of the Y element in the positive electrode material can be 0.01wt%, 0.03wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.12wt%, 0.15wt%, 0.18wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% or any value within the range formed by any two of the above values.
[0049] Among them, the Y element at least includes Y1 element, and the Y1 element contains at least one element selected from Zr, Sr, Ba, Ca, etc. Such elements are doped into the bulk phase to inhibit lithium-nickel mixing and reduce the change in unit cell volume during the charge and discharge process, thereby effectively inhibiting the generation of cracks in the crystal during the charge and discharge process and improving the first coulomb efficiency and discharge capacity of the material.
[0050] The Y element also includes at least a Y2 element, and the Y2 element includes at least one of Al, Ti, Mg, Y, Cu, W, Nb, La, Ce, Mo, Sn and Ta. Such elements are doped into the bulk phase to limit the irregular growth of crystal particles and the formation of particles with excessively large aspect ratios, which is beneficial for the aspect ratio of the crystal particles to be 1 to 1.6.
[0051] The positive electrode material provided in the embodiment of the present application can effectively reduce the gas production of the positive electrode material during the battery cycle by controlling the proportion of the number of cracks in the positive electrode material to 1.5%~11%. In addition, by controlling the average aspect ratio M / N of a single particle in the positive electrode material to satisfy 1≤M / N≤1.6, the aspect ratio of the particles within this range is relatively low, and the crystal particles with a low aspect ratio have a high roundness. The improved roundness is conducive to reducing the specific surface area of the positive electrode material, and the smaller specific surface area is conducive to reducing the direct contact between the positive electrode material and the electrolyte, thereby reducing the generation of side reactions, and is conducive to improving the long-term cycle performance, high temperature storage performance and gas production performance of the positive electrode material. Therefore, the present application can effectively improve the cycle stability of the positive electrode material, improve the cycle performance of the material, and improve the compaction density of the pole piece, so that the positive electrode material has a good capacity, and at the same time effectively reduce the gas production of the positive electrode material after being prepared into a battery.
[0052] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nano-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.
[0053] It can be understood that a single grain in the present application can be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. "Quasi-secondary particles" refer to those formed by the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particles is usually between 1μm-6μm. In general, the roundness of the particles of "quasi-secondary particles" is lower than that of the above-mentioned conventional "secondary particles".
[0054] It should be further explained that the "single crystal" in the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more of "single crystal-like morphology" positive electrode materials, which only show a large particle size similar to a single crystal in size, which is different from a polycrystal composed of many small primary particles.
[0055] The embodiment of the present application also provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing. The electrode assembly includes a separator, a negative electrode sheet and a positive electrode sheet, and the separator is disposed between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet includes the aforementioned positive electrode material.
[0056] Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode material. The positive electrode current collector may be aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0057] In some embodiments, the outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, or the like.
[0058] In some embodiments, the electrode assembly may be a laminated structure, which is formed by alternately stacking a positive electrode sheet, a separator, and a negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.
[0059] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be a composite current collector disclosed in any prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium-ion battery, a sodium-ion battery, a solid electrolyte battery, etc., without limitation herein.
[0060] like Figure 1 and Figure 2As shown in the figure, they are schematic diagrams of lithium removal and lithium insertion during the charging and discharging process of a lithium-ion battery prepared by using the positive electrode material provided in the embodiment of the present application. Figure 1 As shown in , when a lithium-ion battery is charged, lithium ions are released from the positive electrode and embedded in the negative electrode; Figure 2 As shown, when a lithium-ion battery is discharged, lithium ions are released from the negative electrode and embedded back into the positive electrode.
[0061] The aforementioned cathode material was used in button cells to evaluate the battery cycle performance. At room temperature (25°C), after 50 cycles at 1C / 1C, the battery cycle retention rate was ≥96%. This indicates that the aforementioned cathode material can effectively improve the battery cycle performance, and the battery gas production during the cycle is low, not exceeding 1.4mL, and even reduced to less than 1mL.
[0062] The present application also provides a method for preparing the aforementioned positive electrode material, which specifically comprises the following steps: Step S1, mixing a precursor, a lithium salt and an additive containing the Y element to form a mixture, and sintering the mixture once to obtain a primary sintered product.
[0063] Wherein, Y is selected from the oxide, peroxide, hydroxide, chloride, carbonate, sulfate, phosphate or combination of at least one element among Al, Ti, Zr, Sr, Mg, Y, Ba, Cu, W, Nb, La, Ce, Mo, Sn, Ta and Ca.
[0064] In some embodiments, based on the mass of the precursor, the mass proportion of the additive containing the Y element is 0.01 wt% to 0.5 wt%. For example, the mass proportion of the additive containing the Y element can be 0.01 wt%, 0.03 wt%, 0.05 wt%, 0.08 wt%, 0.1 wt%, 0.12 wt%, 0.15 wt%, 0.18 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, or any value within the range formed by any two of the above values.
[0065] The Y element at least contains Y1 element, and the Y1 element includes at least one element of Zr, Sr, Ba, Ca, etc. The additive containing such elements can be used as a flux. Such elements can be doped into the bulk phase to inhibit lithium-nickel mixing and reduce the volume change of the unit cell during the charge and discharge process, thereby effectively inhibiting the generation of cracks in the crystal during the charge and discharge process, and improving the initial coulomb efficiency and discharge capacity of the material. By adjusting the amount of such flux components containing the Y1 element, it is beneficial to form a lithium nickel cobalt oxide single crystal positive electrode material with good dispersion, suitable grain size and small lithium-nickel mixing. The primary particles with good dispersion can form a uniform coating layer, prevent the new surface interface from being exposed due to the fragmentation of the agglomerated particles during the rolling process of the pole piece, avoid the newly exposed surface particles of the positive electrode material from directly contacting the electrolyte, and inhibit side reactions, which is beneficial to improve the initial coulomb efficiency, capacity, structural stability, thermal stability and long cycle stability of the material. Among them, based on the mass of the precursor, the mass proportion of the effective elements in the flux containing the Y1 element is 0.01wt%~0.5wt%, for example, it can be 0.01wt%, 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt% or any value within the range formed by any two of the above values.
[0066] The Y element at least includes a Y2 element, and the Y2 element may include at least one of Al, Ti, Mg, Y, Cu, La, Ce, Sn, W, Mo, Nb, Ta and other elements. Additives containing such elements may be used as inhibitors. Doping such elements into the bulk phase can limit the irregular growth of particles and the formation of particles with excessively large aspect ratios, which is beneficial for particles with an aspect ratio of 1 to 1.6. By adjusting the amount of the Y2 element and other inhibitor components added, it is beneficial to form primary particles with good dispersibility and a nickel cobalt manganese oxide lithium positive electrode material with a small aspect ratio. The positive electrode material with a small aspect ratio has a more regular shape, which can prevent the agglomerated particles from breaking and exposing new surface interfaces during the rolling process of the pole piece, avoid direct contact between the newly formed surface interface and the electrolyte, and inhibit side reactions, which is beneficial to improving the structural stability, thermal stability, long-term cycle performance and gas production performance of the material. Among them, based on the mass of the precursor, the mass proportion of the effective element in the inhibitor containing the Y2 element is 0.01wt%~0.5wt%, for example, it can be 0.01wt%, 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt% or any value within the range formed by any two of the above values.
[0067] In addition, CaO2, Na2O2, KMnO4 and other substances can be added to the mixture as oxygen supplements to increase the oxygen partial pressure, which is beneficial to the growth of particles, inhibits the formation of surface rock salt phase, and is beneficial to improve the first coulomb efficiency, capacity, structural stability, thermal stability and long cycle performance of the positive electrode material. Among them, based on the mass of the precursor, the mass of this type of oxygen supplement accounts for 0.01wt%~1wt%.
[0068] Step S1 is specifically to apply 5MPa~50MPa pressure to the mixture, hold the pressure for 1min~5min, and then place it in an oxygen atmosphere for sintering. Among them, the first sintering process includes two stages of sintering. The sintering temperature of the first stage is not higher than 500℃ (usually 300℃~500℃), and the time is 6h~10h. The purpose is to melt the molten salt and make the additives diffuse evenly in the mixture. The sintering temperature of the second stage is not higher than 880℃ (usually 550℃~880℃), and the time is 4h~12h, which can make the molten salt fully react with the precursor in the oxygen atmosphere, which is conducive to the formation of single crystal materials. Through two-stage gradient temperature sintering, it is conducive to the formation of particles, and the number of cracks in the particles can be controlled at the same time. Among them, within the above range, as the temperature increases and the holding time is extended, the small particles and micropowders can be further fused, and the number of particle cracks can be reduced.
[0069] In some embodiments, the first stage sintering temperature is further 400°C to 450°C. For example, the temperature can be 410°C, 420°C, 430°C, 440°C, 450°C, or any value within the range of any two of the above values. The first stage sintering holding time is further 7h to 9h. For example, the holding time can be 7h, 8h, 9h, or any value within the range of any two of the above values.
[0070] In some embodiments, the second stage sintering temperature can further be 700°C~860°C. Exemplarily, the second stage sintering temperature can be 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C or any value in the range formed by any two of the above values. The second stage sintering holding time is further 6-10h. Exemplarily, the holding time can be 6h, 7h, 8h, 9h, 10h or any value in the range formed by any two of the above values.
[0071] In some embodiments, in step S1, the lithium salt may include any one of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate or lithium oxalate, or a combination of at least two thereof, preferably lithium hydroxide.
[0072] In some embodiments, the mixing method in step S1 is mechanical mixing, which can improve the mixing effect. For example, a high-speed mixer or a VC mixer can be used to mix the materials.
[0073] In some embodiments, the mixing time in step S1 can be 0.3h~2.0h, and an appropriate mixing time can improve the dispersion effect of the material. For example, the mixing time can be 0.3h, 0.4h, 0.5h, 0.7h, 0.8h, 1.0h, 1.2h, 1.5h, 2.0h or any value within the range of any two of the above values.
[0074] In some embodiments, the mixing temperature in step S1 can be 10°C to 50°C, and an appropriate mixing temperature can improve the dispersion effect of the materials. Within this range, the materials can be fully mixed and uniformly mixed, and the side reactions of the mixed raw materials caused by excessively high temperatures can be prevented. The mixing temperature is further 20°C to 40°C. Exemplarily, the mixing temperature can be 10°C, 15°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, or any value within the range of any two of the above values.
[0075] In some embodiments, in step S1, the material is sintered once, and the content of lithium in the lithium salt (i.e., lithium compound) is 0.95-1.05 relative to the total amount of Ni, Co, and N in the above-mentioned precursor in terms of molar ratio. Specifically, the general formula of the precursor can be Ni x Co y N 1-x-y O2, 0.5≤x<1, 0≤y≤0.30, N element includes at least one of Mn and Al. The lithium content ratio is within the above range, which can not only reduce the degree of Li / Ni cation mixing, but also prevent the residual lithium on the surface of the primary sintering product from being too high, affecting the processing performance and safety performance. The lithium content ratio in the lithium salt is further 0.99~1.02. Exemplarily, the lithium content ratio in the lithium salt can be 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.05 or any value within the range composed of any two of the above values.
[0076] In some embodiments, the sintering in step S1 is carried out in an atmosphere with an oxygen content of ≥ 95%. Sufficient oxygen can promote the 2+ To you 3+ conversion, reducing Li / Ni cation mixing and increasing the capacity of the positive electrode material.
[0077] Step S2, crushing the primary sintered product, and performing secondary sintering on the crushed primary sintered product, wherein the secondary sintering is a multi-stage gradient temperature sintering process to obtain a secondary sintered product.
[0078] Specifically, the primary sintered product is subjected to air flow pulverization, and the particles of the pulverized material meet the aspect ratio of 1 to 1.4 and the particle size is 1 μm to 3 μm, and then the pulverized material is subjected to a second sintering. The particle size of the pulverized material is reduced, which is conducive to improving the dispersibility of the single crystal particles, forming a uniform coating layer, and inhibiting the direct contact between the electrolyte and the active material, which is conducive to improving the first coulomb efficiency, capacity, structural stability, thermal stability and long cycle stability of the material.
[0079] The second sintering temperature setting is a two-stage type, high temperature first and then low temperature, where the high temperature sintering temperature is 750℃~980℃, the time is 8~16h, which can effectively promote the growth of particles. After high temperature sintering, low temperature sintering is carried out, the low temperature sintering temperature is 500~900℃, the time is 3~10h, and the low temperature sintering process can effectively eliminate the lattice internal stress. In addition, the temperature difference between high temperature and low temperature is less than 300℃.
[0080] In some embodiments, the temperature of the high temperature sintering stage is further 800-950°C. Exemplarily, the temperature can be 750°C, 800°C, 830°C, 860°C, 890°C, 920°C, 950°C, 980°C or any value within the range formed by any two of the above values.
[0081] In some embodiments, the temperature of the low temperature sintering stage is further 600-800°C. Exemplarily, the temperature can be 500°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or any value within the range formed by any two of the above values.
[0082] In this step, the temperature and time of the high-temperature sintering stage are controlled to achieve the embedding of lithium ions, promote the growth of crystals, control the aspect ratio of the crystal particles to be relatively low, make the particles more rounded, and reduce the specific surface area; then, the temperature and time of the low-temperature sintering are controlled through holes to further embed lithium ions, and at the same time, it can also play a role in annealing, effectively eliminate the stress within the lattice, repair the microcrystalline boundaries, and reduce the number of cracks in the positive electrode material.
[0083] Step S3, crushing the secondary sintered product to obtain a crushed secondary sintered product.
[0084] The average aspect ratio M / N of the particles of the positive electrode material satisfies: 1≤M / N≤1.6, wherein M is the length of the longest straight side of a single particle, and N is the length of the straight side perpendicular to the midpoint of the longest straight side.
[0085] Specifically, the secondary sintering product is subjected to air flow crushing, the crushing process parameters are controlled, and the grinding body mass is controlled to be 10%~60% of the upper limit of the sample amount processed by the equipment, the crushing air pressure is controlled to be 20%~90% of the upper limit of the equipment pressure, the aspect ratio of the crushed crystal particles is 1~1.6, and the crystal particle size is 1μm~6μm.
[0086] In this step, the amount of the grinding body is 10% to 60% of the upper limit of the equipment. For example, the upper limit of the sample amount processed by the small airflow pulverizer is 3 kg, and the amount of the grinding body is 0.3 kg to 1.8 kg. Within this range, the particles can be evenly dispersed to avoid cracks due to excessive collision of particles, and the efficiency of airflow crushing can be ensured. The amount of the grinding body is further 20% to 50% of the upper limit of the equipment. Exemplarily, the amount of the grinding body can be 10%, 20%, 30%, 40%, 50%, 60% of the upper limit of the equipment or any value within the range composed of any two of the above values.
[0087] In this step, the pulverizing air pressure is controlled at 20% to 90% of the upper limit of the equipment pressure. For example, the upper limit of the pulverizing air pressure of a small air flow mill is 1 MPa, and the pulverizing air pressure is 0.2 MPa to 0.9 MPa. Within this range, the pulverizing air pressure is moderate, so that too many cracks are not produced due to strong collisions caused by excessive pulverizing air pressure, and insufficient particle collisions are not caused due to too small pulverizing pressure, which leads to the primary particles not being dispersed. The pulverizing air pressure is further controlled at 30% to 80% of the upper limit of the equipment pressure, and the pulverizing air pressure is further controlled at 40% to 70% of the upper limit of the equipment pressure. Exemplarily, the pulverizing air pressure can be controlled at 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% of the upper limit of the equipment pressure or any value within the range composed of any two of the above values.
[0088] Step S4, mixing the crushed secondary sintered product with a coating agent, and sintering the mixture to obtain the positive electrode material.
[0089] In some embodiments, the coating sintering temperature may be 250°C to 850°C, 4h to 10h. For example, the sintering temperature may be 250°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 850°C, or any value within the range formed by any two of the above values, and the sintering time may be 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range formed by any two of the above values.
[0090] In some embodiments, the capping agent may include at least one of Al2O3, AlOOH, ZrO2, Co3O4, Co(OH)2, CoOOH, TiO2, WO3, Nb2O5, MoO3 and the like.
[0091] In some embodiments, the mass ratio of the coating agent to the crushed secondary sintered product may be 0.05 wt% to 3 wt%. For example, the coating agent may account for 0.05 wt%, 0.1 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, or any value within the range formed by any two of the above values.
[0092] In the preparation process of the positive electrode material of the present application, firstly, by controlling the flux, oxygen supplement, sintering temperature curve and gas crushing process parameters, the crack ratio of the powder material can be effectively optimized and the gas production performance of the positive electrode material can be improved. In addition, on the basis of optimizing the crack ratio of the powder material, further by optimizing the inhibitor and the sintering temperature curve, the aspect ratio of the crystal particles can be effectively controlled, the crushing of the positive electrode material during the pole piece rolling process can be reduced, and the gas production performance of the battery can be improved.
[0093] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0094] Embodiment 1: Step S1, the precursor Ni 0.6 Co 0.1 Mn 0.3 O, LiOH·H2O, flux SrO, inhibitor H2WO4, oxygen supplement CaO2 are mixed evenly in a high-speed mixer, wherein LiOH·H2O and Ni 0.6 Co 0.1 Mn 0.3 The molar ratio of O is 1.03, SrO, H2WO4, CaO2 and Ni 0.6 Co 0.1 Mn 0.3 The mass ratios of O are 0.15wt%, 0.15wt%, and 0.15wt% respectively.
[0095] The mixture was subjected to a pressure of 50 MPa for 5 minutes, kept at 450°C for 7 hours in an oxygen atmosphere at a furnace pressure of 12±4 Pa, and then heated to 800°C for 8 hours to obtain a primary sintered product.
[0096] Step S2, the primary sintered product is pulverized by a small air flow mill, the grinding mass is 0.6 kg, and the pulverizing pressure is 0.4 MPa. The gas-crushed material is subjected to secondary sintering, the first stage temperature is set at 950°C, and the temperature is kept for 10 hours, and the second stage temperature is set at 800°C, and the temperature is kept for 6 hours, to obtain a secondary sintered product.
[0097] Step S3, the above-mentioned secondary sintered product is subjected to air flow pulverization by a small air flow pulverizer, the pulverization process parameters are controlled, the grinding body amount is controlled to be 0.8kg, the pulverization air pressure is controlled to be 0.5MPa, the aspect ratio of the crystal particles after pulverization is 1.48, and the average particle size is 2.2μm, to obtain the secondary sintered product after air pulverization.
[0098] Step S4, mixing the gas-crushed secondary sintered product with the coating agent Al2O3, the mass ratio of the coating agent to the gas-crushed secondary sintered product is 0.2wt%, the shearing action during the mixing process can further reduce the aspect ratio of the single crystal particles, and sintering the mixture at 500°C for 8h in an oxygen atmosphere to obtain an Al-coated ternary single crystal material.
[0099] Example 2 The difference from Example 1 is that in step S1, based on the mass of the precursor, the mass proportion of SrO is 0.30wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0100] Example 3 The difference from Example 1 is that in step S3, the amount of the grinding body is 1.6 kg and the crushing gas pressure is 0.7 MPa. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0101] Example 4 The difference from Example 1 is that in step S1, based on the mass of the precursor, the mass of H2WO4 accounts for 0.4wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0102] Example 5 The difference from Example 1 is that in step S1, based on the mass of the precursor, the mass proportion of H2WO4 is 0.05wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0103] Example 6 The difference from Example 1 is that in step S1, the primary sintering process is adjusted from keeping warm at 450° C. for 7 hours to keeping warm at 300° C. for 5 hours. The other steps are basically the same as Example 1, please refer to Example 1.
[0104] Example 7 The difference from Example 1 is that in step S1, the primary sintering process is adjusted from keeping at 800° C. for 8 hours to keeping at 700° C. for 6 hours. The other steps are basically the same as Example 1, please refer to Example 1.
[0105] Example 8 The difference from Example 1 is that in step S2, the secondary sintering process: the first stage of 950° C. heat preservation for 10 hours is adjusted to 920° C. heat preservation for 6 hours. The other steps are basically the same as Example 1, please refer to Example 1.
[0106] Example 9 The difference from Example 1 is that in step S2, the secondary sintering process: the second stage of 800° C. heat preservation for 6 hours is adjusted to 600° C. heat preservation for 4 hours. The other steps are basically the same as Example 1, please refer to Example 1.
[0107] Example 10 The difference from Example 1 is that in step S1, based on the mass of the precursor, the mass of the flux SrO accounts for 0.2wt%, and the mass of the inhibitor H2WO4 accounts for 0.1wt%; the sintering process in step S2 is: keeping the temperature at 945°C for 9h and then cooling to 820°C for 5h.
[0108] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0109] Embodiment 11 The difference from Example 1 is that in step S1, the precursor is Ni 0.7 Co 0.1 Mn 0.2 O, LiOH·H2O is changed to Li2CO3, and flux SrO is changed to ZrO2. Other steps are basically the same as those in Example 1, please refer to Example 1.
[0110] Example 12 The difference from Example 1 is that in step S1, the precursor is Ni 0.8 Co 0.1 Mn 0.1 O, the flux SrO is changed to ZrO2, and the inhibitor is changed to MoO3. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0111] Comparative Example 1 The difference from Example 1 is that SrO is not added in step S1. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0112] Comparative Example 2 The difference from Example 1 is that the airflow crushing process is not performed in step S3. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0113] Comparative Example 3 The difference from Example 1 is that the crushing air pressure in step S3 is controlled at 95% of the upper limit. The other steps are basically the same as Example 1, please refer to Example 1.
[0114] Comparative Example 4 The difference from Example 1 is that the amount of the grinding body in step S3 is 70% of the upper limit of the equipment. The other steps are basically the same as Example 1, please refer to Example 1.
[0115] Comparative Example 5 The difference from Example 1 is that the mass proportion of flux SrO is 0.05wt%, and the mass proportion of inhibitor H2WO4 is 0.05wt%. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0116] Comparative Example 6 The difference from Example 1 is that the mass proportion of flux SrO is 0.3wt%, and the mass proportion of inhibitor H2WO4 is 0.5wt%. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0117] Comparative Example 7 The difference from Example 1 is that the mass proportion of flux SrO is 0.4wt%, the mass proportion of inhibitor H2WO4 is 0.1wt%; the 950℃ heat preservation for 10h in step S2 is reduced to 930℃ heat preservation for 10h. The other steps are basically the same as Example 1, please refer to Example 1.
[0118] The following method was used to perform performance tests on the positive electrode materials obtained in the above Examples 1-12 and Comparative Examples 1-7.
[0119] 1. Aspect ratio test: Sample preparation: Take the crushed positive electrode material matrix, use a conductive adhesive with a length of 0.5 mm to pick up the material. After the material is taken, use an ear-cleaning bulb to blow the conductive adhesive surface with the material 10 times.
[0120] Electron microscope photography: A scanning electron microscope (SEM) was used to conduct the test under the electron beam condition of 5kV / 10mA. The picture with more particles was selected, and 10 electron microscope photos were taken at a magnification of 3K.
[0121] Aspect ratio test: Use Nano Measure software to measure the length M of the longest straight side of the single crystal particle in each electron microscope photo, and the length N of the straight side perpendicular to the midpoint of the longest straight side. The average aspect ratio of each single crystal particle is M / N.
[0122] 2. Crack test: Test on the proportion of particles with cracks in positive electrode materials: First, take the powder positive electrode material, mix the powder positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, add NMP (N-methylpyrrolidone) to make a uniform slurry and apply it on aluminum foil, dry it in an oven, and make a pole piece. Use the pole piece as a sample, and according to the standardized process of cross-section sample preparation, use an electron transmission microscope to focus the ion beam into a small-sized ion beam to bombard the surface of the sample to achieve sample peeling. The stripped sample is tested by scanning electron microscopy (SEM). Under a field of view of 3 k, the field of view of different areas is counted, and the proportion of the number of positive electrode material particles with cracks to the total number of positive electrode material particles is counted, and the number of cracks is characterized by the ratio. The test results of this application are statistical results obtained by randomly selecting cross sections of about 300 positive electrode material particles in the SEM image as samples. The SEM test requires random sampling of positive electrode materials and random selection of areas. The SEM images obtained from the test can represent the average level of the positive electrode materials tested. Since the pole pieces are not rolled during the production process in this test method, the crack number ratio obtained from the test can be regarded as the crack particle number ratio of the positive electrode material in the powder state.
[0123] Test on the proportion of positive electrode material particles with cracks in positive electrode sheets: First, take the powder positive electrode material, mix the powder positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, add NMP (N-methylpyrrolidone) to make a uniform slurry and apply it on aluminum foil, dry it in an oven, and roll it under a pressure of 10 Mpa to make a sheet. Use the sheet as a sample, and according to the standardized process of cross-section sample preparation, use an electron transmission microscope to focus the ion beam into a small-sized ion beam to bombard the surface of the sample to achieve sample peeling. The stripped sample is tested by a scanning electron microscope (SEM). Under a field of view of 3 k, the field of view of different areas is counted, and the proportion of the number of positive electrode material particles with cracks to the total number of positive electrode material particles is counted, and the number of cracks is characterized by the ratio. The test results of this application are statistical results obtained by randomly selecting cross sections of about 300 positive electrode material particles in the SEM image as samples. The SEM test requires random sampling of positive electrode materials and random selection of areas. The SEM image obtained from the test can represent the average level of the positive electrode material tested.
[0124] 3. XRD test of positive electrode materials: X-ray diffraction phase analysis (XRD): The phase-free structure of the positive electrode material was analyzed using a Rigaku X-ray diffractometer (XRD). The specific parameters were as follows: scanning range 10°-80°, scanning speed 2° / min, and step length 0.005°.
[0125] 4. Particle size test: Nano Measurer software was used to test the average particle size of single crystal materials. The specific method is as follows: Use a scanning electron microscope to analyze the morphology of single crystal materials, use Nano Measurer software to measure the particles in the SEM under a 3000x view, take the long side value as the particle size, count all particles with clear morphology in the SEM, and take the average value.
[0126] 5. Compaction density test: Using the American Carver 4350 tester, 1g of sample was weighed and placed in a mold, pressed with a pressure of 3T for 30s. After pressing, the height was tested and the compacted density was calculated.
[0127] 6. Specific surface area test: The specific surface area of the material is tested using the Microbeam 3020 nitrogen adsorption method.
[0128] Finished product pretreatment: weigh the mass of the empty sample tube m1; take 3g of sample, vacuum degas at 300℃ for 1h, and weigh the mass of the sample tube m2 after cooling; sample mass m=m2-m1.
[0129] Sample testing: The sample tube is placed in liquid nitrogen, and the nitrogen adsorption capacity V of the sample is measured at a series of relative pressures P / P0 to obtain the adsorption isotherm.
[0130] The isothermal adsorption curve was fitted, and the monolayer saturated adsorption capacity Vm was calculated according to the slope and intercept; then the specific surface area was calculated based on Vm.
[0131] 7. Surface residual lithium test: The total amount of lithium compounds on the surface of the positive electrode material is tested by a potentiometric titrator, specifically by hydrochloric acid titration, and then the amount of consumed hydrochloric acid is converted into the amount of lithium compounds.
[0132] 8. Battery production and performance testing The electrochemical performance of the prepared cathode material was evaluated by using a button half-cell. The specific method is as follows: the cathode material, SP and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 93:5:2, NMP was added at a solid content of 50%, and a high-speed disperser was used to adjust the viscous slurry. The slurry was evenly coated on the aluminum foil with a scraper, and after drying in an oven at 80°C, the slurry was rolled and cut into a cathode electrode sheet with a diameter of 14 mm. A lithium sheet with a diameter of 16 mm was used as the negative electrode sheet, a Celgard polyethylene PP film was used as the separator, and a carbonate solution of LiPF6 (DEC / EC volume ratio 1:1) with a concentration of 1 mol / L was used as the electrolyte. The assembly was carried out in a glove box filled with argon.
[0133] The LAND battery testing system was used to conduct capacity, first efficiency and rate performance tests at 25°C, 3.0V-4.4V. The reference capacity was set to 200 mA / g, and 1C corresponded to a current density of 200 mA / g.
[0134] 9. Gas production performance test: The storage gas production performance of the positive electrode material was evaluated by using a basic soft-pack battery. The specific method is as follows: the positive electrode material, PVDF, SP, and CNT were weighed in a mass ratio of 97.0:1.0:1.5:0.5, NMP was added according to a solid content of 50%, and a high-speed dispersant was used to make a viscous slurry. The slurry was evenly coated on the aluminum foil with a scraper, and then dried in an oven at 80°C, and then rolled and cut into 4cm×8cm positive electrode sheets; the graphite negative electrode, SP, CMC, and SBR were weighed in a mass ratio of 96:1.0:1.2:1.8, dispersed into a slurry, coated on a copper foil, and cut into 4cm×8cm negative electrode sheets. The positive and negative electrode sheets were assembled into a basic soft-pack battery, charged to the target voltage after formation, and then stored in a 60°C oven for 21 days. The volume difference before and after storage was tested by the drainage method, which was the gas production.
[0135] The corresponding test results of the positive electrode materials of Examples 1-12 and Comparative Examples 1-7 are shown in Tables 1 and 2 below.
[0136] Table 1 Table 2 Figure 3 and Figure 4 The SEM photos of the positive electrode materials of Example 1 and Comparative Example 1 at 3000 times magnification are shown in FIG. Figure 3 It can be seen that the primary particles of the positive electrode material obtained in Example 1 are well dispersed and uniform; Figure 4 It can be seen that the primary particles of the positive electrode material obtained in Comparative Example 1 are obviously agglomerated, and there are some particles that are not fully grown. Figure 5 and Figure 6 The cross-sectional SEM images of the positive electrode materials of Example 1 and Comparative Example 1 at 5000 times magnification are shown in FIG. Figure 5 It can be seen that the positive electrode material obtained in Example 1 has fewer cracks; Figure 6 It can be seen that the positive electrode material obtained in Comparative Example 1 has more cracks.
[0137] Depend on Figure 7It can be seen that the single crystal positive electrode material obtained in Example 1 has a cycle performance significantly better than that of Comparative Example 1. In addition, combined with Table 1, it can be seen that the cycle performance of the battery prepared by the positive electrode materials of Examples 1-12 is significantly better than that of Comparative Examples 1-7. It can be seen from Table 1 that after the single crystal positive electrode material obtained in Example 1 is prepared into a battery, the storage gas production is significantly lower than that of Comparative Examples 1-3.
[0138] Examples 1, 11 and 12 adjust the Ni content in the precursor. For ternary positive electrode materials with different nickel contents, the preparation method of the embodiments of the present application is adopted to ensure that the aspect ratio of the single crystal particles in the positive electrode material is in the range of 1 to 1.6 (specifically 1.3), the particles are relatively round, and the number of cracks accounts for less than 11%. The single crystal positive electrode material that meets the above conditions has good cycle performance. After being prepared into a battery, it can effectively reduce the gas production of the battery and improve the storage performance.
[0139] Compared with Example 1, Example 2 increases the amount of flux added, which can significantly reduce the proportion of cracks in the positive electrode material, reducing the crack proportion from 8.3% in Example 1 to 1.9%, improving the cycle performance of the battery, and reducing the gas production. The gas production can be reduced from 0.91 mL in Example 1 to 0.76 mL.
[0140] Compared with Example 1, Example 3 increases the amount of grinding media and the crushing air pressure in step S3, which can effectively disperse the single crystal particles evenly without causing cracks due to excessive collisions of particles, while ensuring the efficiency of air flow crushing.
[0141] Compared with Example 1, Example 4 increases the amount of inhibitor added, which can reduce the particle aspect ratio of the positive electrode material from 1.42 in Example 1 to 1.13, and can also reduce the proportion of cracks in the positive electrode material from 8.3% in Example 1 to 7.8%, thereby improving the cycle performance of the battery and reducing the gas production.
[0142] Compared with Example 1, Example 5 reduces the amount of inhibitor added, and the inhibitory effect on the crystal growth of the positive electrode material is weakened. Therefore, the particle aspect ratio of the positive electrode material is increased compared with Example 1, and the number of particles satisfying 1≤X / Y≤1.6 accounts for less than 90%, the gas production is increased, and the cycle performance is reduced.
[0143] Compared with Example 1, Examples 6 and 7 both lower the temperature of the primary sintering in step S1 and shorten the holding time. The fusion of small particles and micropowder is not as complete as in Example 1. Therefore, the number of cracks in the single crystal particles of Examples 6 and 7 increases, and the gas production also increases.
[0144] Compared with Example 1, Example 8 reduces the temperature of the secondary sintering in step S2, shortens the holding time, and reduces the growth time of the single crystal particles. The crystal particles are not well repaired as in Example 1, and the unit cell of the grains is smaller. As a result, the number of cracks in the positive electrode material of Example 8 increases, the half-peak width is larger, and the gas production increases.
[0145] Compared with Example 1, Example 9 reduces the secondary sintering insulation temperature and time in step S2, the lattice internal stress of the single crystal particles cannot be effectively eliminated, and the crystal particles are not well repaired as in Example 1. The number of cracks in the positive electrode material obtained in Example 9 increases, and the gas production also increases.
[0146] Compared with Example 1, Example 10 increases the flux content, reduces the inhibitor content, and adjusts the sintering temperature and sintering time, which can reduce the number of cracks and reduce the particle aspect ratio of the positive electrode material, thereby obtaining the best cycle performance and the lowest gas production.
[0147] Compared with Example 1, Example 11 increases the nickel content in the precursor, which can improve the capacity of the positive electrode material while ensuring a low aspect ratio and a low crack ratio, so that the positive electrode material has good cycle performance, higher capacity and lower gas production.
[0148] Compared with Examples 1 and 11, Example 12 further increases the nickel content, and by combining corresponding fluxes and inhibitors, it is possible to further increase the capacity of the positive electrode material while ensuring a low aspect ratio and a low crack ratio, so that the positive electrode material has good cycle performance, higher capacity and lower gas production.
[0149] In Comparative Example 1, no polar flux was added, and the number of cracks accounted for a high proportion, reaching 12.6%, exceeding 11%, and the cycle performance of the positive electrode material was significantly reduced, and the gas production was significantly increased. Compared with Example 1, in Comparative Example 2, after the secondary sintering, no air flow crushing was performed, and the number of cracks in the positive electrode material accounted for a high proportion, reaching 13.5%, exceeding 11%, and the cycle performance of the positive electrode material was significantly reduced, and the gas production was significantly increased.
[0150] In Comparative Example 3, the pulverizing air pressure in step S3 was increased. The pulverizing air pressure was too high, causing too many collisions among the crystal particles and producing too many cracks. The number of cracks accounted for 11.8%, exceeding 11%, resulting in more gas production and poor cycle performance of the prepared battery.
[0151] In Comparative Example 4, the amount of grinding body in step S3 is increased. The amount of grinding body is too high, resulting in too many collisions between crystal particles and too many cracks. The number of cracks accounts for 12.0%, which exceeds 11%, resulting in more gas production and poor cycle performance of the prepared battery.
[0152] Therefore, compared with Examples 1-12, the proportion of the number of cracks in the positive electrode material in Comparative Example 1-7 is not in the range of 1.5% to 11%, and the aspect ratio is not in the range of 1 to 1.6, and the cycle performance and gas production performance of the positive electrode material are poor.
[0153] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A positive electrode material, characterized in that: The ratio of the number of particles with cracks in the positive electrode material to the total number of particles is 1.5%~11%, and the average aspect ratio M / N of the particles of the positive electrode material satisfies: 1≤M / N≤1.6, wherein M is the length of the longest straight side of a single particle, and N is the length of the straight side perpendicular to the midpoint of the longest straight side.
2. The positive electrode material according to claim 1, characterized in that In the XRD spectrum of the positive electrode material, the positive electrode material has a diffraction peak within 44°~45°, and the half-peak width of the diffraction peak is 0.150°~0.200°.
3. The positive electrode material according to claim 1, characterized in that The number of particles satisfying 1≤M / N≤1.6 in the positive electrode material accounts for no less than 90%.
4. The positive electrode material according to claim 1, characterized in that The general formula of the positive electrode material is as follows: Li a Ni x Co y N 1-x-y-b Y b O2, wherein 0.95≤a≤1.05, 0.5≤x<1, 0≤y≤0.30, 0.001≤b≤0.01, the N element includes at least one of Mn and Al, and the Y element includes at least one of Al, Ti, Zr, Sr, Mg, Y, Ba, Cu, W, Nb, La, Ce, Mo, Sn, Ta and Ca.
5. The positive electrode material according to claim 4, characterized in that The Y element includes at least a Y1 element and a Y2 element, the Y1 element includes at least one element of Zr, Sr, Ba and Ca, and the Y2 element includes at least one element of Al, Ti, Mg, Y, Cu, W, Nb, La, Ce, Mo, Sn and Ta.
6. The positive electrode material according to claim 4, characterized in that The mass proportion of the Y element in the positive electrode material is 0.01wt%~0.5wt%.
7. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The positive electrode material comprises a plurality of primary particles, and the average particle size of the primary particles is 1 μm to 6 μm; (2) The positive electrode material is a single crystal material, and the positive electrode material contains single particles with the same orientation; (3) The particle size of the positive electrode material satisfies: D min <1μm,2.0μm<D V,50 <4.5μm, D max <15μm,0.8<(D V,90 -D V,10 ) / D V,50 <1.6; (4) The specific surface area of the positive electrode material is 0.1 m 2 / g ~1.6 m 2 / g; (5) The oil absorption value of the positive electrode material is 10 mL to 40 mL per 100 g; (6) The surface residual alkali of the positive electrode material satisfies: LiOH≤0.5wt%, Li2CO3≤0.5wt%; (7) The compaction density of the positive electrode material is 2.5 g / cm 3 ~3.6g / cm 3 .
8. A method for preparing a positive electrode material, characterized in that: The following steps are involved: Mixing a precursor, a lithium salt and an additive to form a mixture, and sintering the mixture once to obtain a primary sintered product; The primary sintered product is crushed, and the crushed primary sintered product is subjected to secondary sintering, wherein the secondary sintering is a multi-stage gradient temperature sintering process to obtain a secondary sintered product; crushing the secondary sintered product to obtain a crushed secondary sintered product; as well as The crushed secondary sintered product is mixed with a coating agent and sintered to obtain the positive electrode material, wherein the ratio of the number of particles with cracks in the positive electrode material to the total number of particles is 1.5%~11%, and the average aspect ratio M / N of the particles of the positive electrode material satisfies: 1≤M / N≤1.6, wherein M is the length of the longest straight side of a single particle, and N is the length of the straight side perpendicular to the midpoint of the longest straight side.
9. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material as described in any one of claims 1 to 7 or the positive electrode material prepared by the method for preparing the positive electrode material as described in claim 8.
10. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material according to any one of claims 1 to 7 or the positive electrode material prepared by the method for preparing the positive electrode material according to claim 8.
Citation Information
Patent Citations
Fe base lithium sale compound anode materials and its making method
CN101188293A
Preparation method of large single crystal lithium ion battery nickel cobalt lithium manganate cathode material
CN110534733A
Secondary battery and electric device
CN115881892A
Positive electrode material, preparation method thereof and battery
CN118073560A
Positive electrode material, secondary battery, and electric device
CN118173773A
Cited By
Low-polarization single-crystal ternary positive electrode material prepared by independent fusion and application thereof
CN120709357A
Positive electrode active material, preparation method thereof and battery
CN121617953A
Positive electrode material, positive electrode sheet, and secondary battery
WO2026046430A1